2022
DOI: 10.1038/s41413-022-00214-z
|View full text |Cite
|
Sign up to set email alerts
|

Type II collagen-positive progenitors are important stem cells in controlling skeletal development and vascular formation

Abstract: Type II collagen-positive (Col2+) cells have been reported as skeletal stem cells (SSCs), but the contribution of Col2+ progenitors to skeletal development both prenatally and postnatally during aging remains unclear. To address this question, we generated new mouse models with ablation of Col2+ cells at either the embryonic or postnatal stages. The embryonic ablation of Col2+ progenitors resulted in the death of newborn mice due to a decrease in skeletal blood vessels, loss of all vertebral bones and absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The same groups presented localized areas of bone remodeling (woven bone), which were heavily stained for COL I and less reactive at the bone chip remnants ( Figures 6B2, B4 —red dashed lines). These fragments of the original bone graft ( Figures 6C2, C4 —red dashed lines), identified by the presence of islands of hypermineralized cartilage, were positively stained for collagen type II ( Figures 6C2, C4 ), suggesting osteochondral bone formation ( Li et al, 2022 ). Nevertheless, the bone chips positively stained for osteocalcin (OC), a late osteogenic marker of bone formation, expressed by early osteocytes, as well as at bone lining osteoblasts at the surface of the bone chips ( Figure 6D2 —red arrows; Figure 6D4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The same groups presented localized areas of bone remodeling (woven bone), which were heavily stained for COL I and less reactive at the bone chip remnants ( Figures 6B2, B4 —red dashed lines). These fragments of the original bone graft ( Figures 6C2, C4 —red dashed lines), identified by the presence of islands of hypermineralized cartilage, were positively stained for collagen type II ( Figures 6C2, C4 ), suggesting osteochondral bone formation ( Li et al, 2022 ). Nevertheless, the bone chips positively stained for osteocalcin (OC), a late osteogenic marker of bone formation, expressed by early osteocytes, as well as at bone lining osteoblasts at the surface of the bone chips ( Figure 6D2 —red arrows; Figure 6D4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides of the similar parts with Osx + cells (osteoblasts, osteocytes and stromal cells underneath growth plate), Col2 + cells also largely expressed in the chondrocytes of articular cartilage, secondary ossification center and growth plate. Whether these Col2 + chondrocytes in secondary ossification center and growth plate caused this GONFH-like phenotype, as it has been reported that the osteogenic commitment of these Col2 + chondrocytes (Shu et al, 2021 ;Li et al, 2022 ). At the age of 3 month, Col2 + chondrocytes in the secondary ossification center and growth plate were almost replaced by Col2 + osteoblasts, osteocytes and stromal cells, while GONFH-like phenotype including fat droplets accumulation and sparse bone trabeculae could be still observed in 6-month-old β-catenin Col2ER mice, indicating that not only Col2 + chondrocytes but all Col2 + cells in different cellular morphology were involved in this GONFH-like phenotype.…”
Section: Discussionmentioning
confidence: 95%
“…Sirius red staining indicates that lack of Sfrp4 leads to a disorganization of collagen fibrils in cortical bone and fracture experiments show that lack of Sfrp4 hinders the periosteal response to bone fracture and callus formation and this was associated with a decrease in the Ctsk-lineage cells. Previous studies have reported that Col2a1 + cells in bone marrow, growth plate and perichondrial/periosteal are skeletal stem cells, and genetic lineage tracing studies, have recently shown that embryonic Col2a1 + cells contribute to cells in the growth plate, trabecular or cortical bone, tendons, and ligaments ( 68 72 ). Our findings that Col2a1 expression is decreased in Sfrp4 -deficient Ctsk-lineage PSCs, are therefore consistent with our hypothesis that absence of Sfrp4 negatively affects the differentiation and functionality of these cells.…”
Section: Discussionmentioning
confidence: 99%